2019
DOI: 10.1159/000497069
|View full text |Cite
|
Sign up to set email alerts
|

Liver Fibrosis, Not Steatosis, Associates with Long-Term Outcomes in Ischaemic Stroke Patients

Abstract: Background: To investigate whether there are differences in long-term all-cause and cardiovascular mortality according to the burden of liver fibrosis or steatosis in patients with ischaemic stroke or transient ischaemic attack (TIA). ­Methods: Consecutive patients with acute ischaemic stroke or TIA who underwent transient elastography (TE) from January 2014 to December 2014 were considered eligible. The influence of liver fibrosis or steatosis, assessed via TE, on long-term outcomes was investigated using Cox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…Accumulating evidence shows that liver fibrosis, not simple steatosis, was a strong predictor of all-cause mortality and cardiovascular morbidity or mortality among the general population [2][3][4][5] because liver fibrosis can exacerbate systemic inflammation, hypercoagulable state, and cerebral atherothrombosis or increase the risk of cardiac arrhythmia [1,6,7]. However, although subclinical liver fibrosis may not be rare in ischemic stroke (IS) patients [8,9], there are very limited data on the association between liver fibrosis and long-term stroke outcomes, especially recurrent IS.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence shows that liver fibrosis, not simple steatosis, was a strong predictor of all-cause mortality and cardiovascular morbidity or mortality among the general population [2][3][4][5] because liver fibrosis can exacerbate systemic inflammation, hypercoagulable state, and cerebral atherothrombosis or increase the risk of cardiac arrhythmia [1,6,7]. However, although subclinical liver fibrosis may not be rare in ischemic stroke (IS) patients [8,9], there are very limited data on the association between liver fibrosis and long-term stroke outcomes, especially recurrent IS.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has demonstrated that liver cirrhosis is associated with an increased risk of stroke, particularly hemorrhagic stroke (6). In addition, a recent study showed liver fibrosis, not simple steatosis, is a strong predictor of long-term mortality in the ischemic stroke population (7). Although these studies highlight a possible relevance between advanced liver diseases and poor stroke outcomes, it is still unsure if these findings can also apply to subclinical liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…As referred before, the importance of liver fibrosis is beyond the liver prognosis[ 18 , 19 ]. Therefore, to improve the prognosis of patients with NAFLD and fibrosis the treatment of concomitant diseases must be a priority.…”
Section: Management Of Liver Fibrosis In Nafldmentioning
confidence: 99%
“…Fibrosis parallels the development of the two major components of chronic liver diseases: Portal hypertension and functional hepatocyte insufficiency. However, the importance of liver fibrosis is beyond “liver prognosis” itself, as it is associated with other adverse clinical outcomes, including cardiovascular events[ 15 ], ischemic stroke[ 16 ], metabolic complications[ 17 ], and all-cause and cardiovascular mortality[ 18 , 19 ]. This could be explained by a more pronounced systemic inflammation profile influencing different organs and systems, and the interaction between them leading to further inflammation and activation of the immune response.…”
Section: Introductionmentioning
confidence: 99%